Melaksanakan Pembelajaran Bahasa Inggris Dengan Cara Yang Variatif Dan Kreatif Guna Mendorong Motivasi Belajar Para Siswa - Yulina Tiwery; Dian Sartin Tiwery; Sefanya Sairiltiata (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
This service activity was carried out by several students from the English Language Education Study Program who are the administrators of the Pattimura University-PSDKU Study Program Student Association (HMPS), Southwest Maluku Regency, which was also attended by 3 lecturers. HMPS English Language Education, which is an internal student organization in campus, apart from organizing academic activity programs, HMPS also provides non-academic activity programs. One of them, HMPS has a role in carrying out Community Service activities which are oriented towards the school community through one of the field I programs "Field of Knowledge and Reasoning". This PKM is realized through learning actions in the classroom with several topics, namely "Transportation, Human Body Parts, and Introducing Yourself" in grades 4, 5 and 6 at SD Inpres Werwaru. Learning English, which is still a challenge today, especially at the elementary school level, is carried out through planned activities in creative ways that are varied and fun for the students. The implementation of PKM in this school was carried out well and received a positive response not only from the Headmaster and Teachers, but also the students expressed their high curiosity during the one more hour teaching and learning process. It is expected that, this activity will provide benefits for students to continue learning and can motivate themselves to learn English from an early age